Kajian penghasilan polipina: the conversion of pineapple leaves to white fabric / Wan Yunus Wan Ahmad … [et al.] - Wan Ahmad, Wan Yunus; Salleh, Jamil; Ahmad, Mohd Rozi; Ab Kadir, Muhammad Ismail; Misnon, Mohd Iqbal; Mohd Nor, Mohd Azlin; Omar, Khadijah; Tumin, Siti Marsinah (Research Management Institute (RMI), 2010)
The Malaysian pineapple leaf fibre (PALF) from Yankee type was converted to fabric through fibre scrapping, hand spinning and hand loom weaving. It was scoured and bleached to remove impurities and turn to natural white colour. The project was to reduce pineapple leaves waste in plantation but a lot of works needs to be carried out to speed up the process of conversion to fibre, yarns and fabric. Process of conversion can be much faster and in larger volume by using suitable machineries and trained workers.